STRATEGI DINAS PERINDUSTRIAN, PERDAGANGAN, KOPERASI, USAHA KECIL DAN MENENGAH (UKM) PROVINSI RIAU DALAM MENJAGA STABILITAS HARGA PANGAN DI KOTA PEKANBARU TAHUN 2023 - Azri, Huriati; Susanto, Agus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Food price stability is a crucial aspect in maintaining food security and public welfare, especially in Pekanbaru City which has a high dependence on food supplies from outside the region. This study aims to analyze the strategies implemented by the Riau Province Industry, Trade, Cooperatives, Small and Medium Enterprises (SMEs) Service in maintaining food price stability and identifying factors that influence the effectiveness of these strategies. This study uses a qualitative method with a descriptive qualitative research type. The location of the study was carried out at the Riau Province Industry, Trade, Cooperatives, Small and Medium Enterprises (SMEs) Service. Data collection techniques through interviews and documentation. Data analysis refers to Fred R. David's strategic management theory, which consists of three main stages, namely strategy formulation, strategy implementation, and strategy evaluation. The results of the study indicate that the Riau Province Industry, Trade, Cooperatives, Small and Medium Enterprises (SMEs) Service has implemented various strategies, such as implementing low-cost market operations, market and distributor inspections, and coordinating with distributors and traders, monitoring food prices periodically and collaboratively. However, the implementation of this strategy still faces obstacles, including the lack of an accurate food distribution recording system, disruptions to distribution channels due to external factors such as natural disasters, and limited local food production that causes dependence on supplies from other regions. The conclusion of this study confirms that the effectiveness of the SMEs Industry, Trade, Cooperatives and Small and Medium Enterprises (Disperindagkop) strategy in maintaining food price stability still needs to be improved. With a more integrated strategy based on accurate data, it is hoped that food price stability in Pekanbaru City can be better maintained, so that community welfare can increase. Keywords: Food price stability, Government Strategy, Food Distribution, Pekanbaru City.